Residential Building. Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
This multi-family housing building is located in a sedimented area of Lisbon, between Rua Presidente Arriaga and Rua do Olival, in front of Jardim 9 de Abril – also called Jardim das Albertas or Jardim da Rocha de Conde de Óbidos –, marked by a wide view over the Tagus River. The four-storey building with facades facing both streets crosses the plot and develops in a U shape, forming a landscaped courtyard, lined with traditional green tiles, to which large glazed areas face. The façade facing the public garden and the river view is equipped with a loggia, a transitional element between the building's interior spaces and the landscape. The loggia is made up of a series of stone pillars that are so thin that they had to be reinforced internally with steel, delimiting balconies – following the vertical and horizontal markings that characterise the adjacent buildings. The northern façade, on the other hand, is, like the wall found there, blind, covered by a creeper that covers the entire surface. The roof is made of a zinc surface composed of multiple waters – subtly evoking the traditional roof –, barely visible from the public space, “establishing a compromise between the memory of the roof and the paradigmatic fl at roofs of contemporary architecture”.